Stupidity in Polish and Bulgarian Phraseologisms with a ‘Head’ Component - Joanna Mleczko (Zeszyty Cyrylo-Metodiańskie)
This paper analyses Polish and Bulgarian phraseologisms containing the lexeme ‘head’ that describe intellectual deficiencies. Most of the phrases studied are based on the metaphor of the head as a container. These phrasemes can be categorised into two main groups: (a) those reflecting faults in the functioning of the mental apparatus, and (b) those indicating the absence of a brain or its substitution with low-value replacements. Another notable group comprises metonymic structures in which ‘head’ represents the concept of a human, often accompanied by pejorative descriptors. The comparative analysis of bilingual material reveals both similarities and differences in the formal structure, semantic content, and imagery characterising the Polish and Bulgarian expressions within this semantic domain. Original title in Polish: Głupota w polskich i bułgarskich związkach frazeologicznych z komponentem ‘głowa’ / ‘глава’.